Framing Smart City in Indonesia's New Capital: Integrating Technology, Culture, and Public Participation - Doktoralina, Caturida Meiwanto; Nugroho, Lucky; Putra, Yananto Mihadi; Prabantoro, Albertus Magnus Putut (Baca Dulu Publisher, 2024)
The relocation of Indonesia's capital from Jakarta to East Kalimantan is a strategic initiative to address critical issues such as traffic congestion, land subsidence, and severe air pollution, highlighting the urgency of enhancing national resilience. This article examines the application of the smart city concept in developing the new Ibu Kota Negara (Nusantara Capital City/IKN), focusing on integrating information and communication technology (ICT), creativity, and community engagement in urban planning while also exploring how these elements can be adapted to IKN and how prospect theory can be leveraged to boost public acceptance. Through a literature review of global smart city implementations, the study finds that applying smart city principles in IKN can significantly improve public service efficiency, environmental sustainability, and quality of life. Prospect theory suggests that well-framed policy communication can increase public support and reduce resistance to change. This research offers valuable insights for policymakers, providing practical recommendations for effective communication strategies and highlighting the importance of adapting the smart city concept to Indonesia's unique socio-economic context to strengthen national resilience.